Worker Education in South Africa: Lessons and contradictions - Vally, Salim; wa Bofelo, Mphutlane; Treat, John (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
Worker education played a crucial role in the development of the trade union movement in South Africa and in the broader struggle for social transformation. This article reviews key moments and dynamics in the trajectory of worker education in South Africa. We argue that international developments, the rise of neoliberalism, and the negotiated compromise between the African National Congress (ANC) and the apartheid state, as well as corporatism resulted in changes to worker education. While the latter as it existed in the past has weakened, the centre of gravity has shifted to community organizations where various forms of learning and creativity continue. Despite the challenges and setbacks of recent years, there remains a significant legacy and influence of the traditions of worker education and militant trade unionism in South Africa, which can and should be drawn upon.